Determination of suitable species that can be used in declining niobium pollution in the atmosphere - Gullizar OZYURT; Halil Baris OZEL; Hakan SEVIK; Hatice COBANOGLU (GSC Online Press, 2024)
This study aimed to determine the most suitable woody species that can be used to reduce niobium (Nb) pollution, which can be harmful and toxic to human and environmental health. Within the scope of the study, samples were taken from the wood part of 16 trees growing under similar growing conditions in Düzce province, one of the 5 most polluted cities in Europe according to the 2021 World Air Pollution Report, and Nb concentrations were determined. As a result, Nb concentration was below the detectable limits in the woods of Pseudotsuga menziesii, Fraxinus excelsior, and Tilia tomentosa. Apart from this, the lowest values were obtained in the woods of Picea orientalis, Pinus pinaster, and Cupressus sempervirens, and the highest values were obtained in the woods of Robinia pseudoacacia and Cedrus atlantica. It was calculated that there was an approximately 522-fold difference between the lowest determined Nb concentration (P. orientalis with 105.5 ppb) and the highest Nb concentration (R. pseudoacacia with 55117.2 ppb). In conclusion, suitable species that can be used to reduce Nb pollution in the air are R. pseudoacacia and C. atlantica.
Keywords: Heavy metal; Niobium; Wood; Phytoremediation; 13. Climate action; 11. Sustainability; 15. Life on land